Recent advances in printed liquid metals for wearable healthcare sensors: a review. (14th July 2022) - Liu, Longhui; Huang, Han; Wang, Xincheng; He, Pei; Yang, Junliang
Abstract: Wearable healthcare sensors can perform real-time health monitoring by tracking various physical signals, physiological signals, as well as electrophysiological activities of the human body. Liquid metals have become an ideal candidate material for wearable healthcare sensors due to their excellent physical and chemical properties, such as high stretchability, high electrical and thermal conductivity, as well as great biocompatibility. Printing techniques present the possibility to fabricate economically efficient, versatile, low-cost and large-area functional electronic devices based on liquid metals. A series of wearable sensors based on liquid metals through printing processes have been designed and reported. Herein, we present a review on the recent advances in printed liquid metals toward wearable healthcare sensors. A detailed landscape view on the properties of liquid metals is provided, following by the overview of printing methods, including direct writing, screen printing, inkjet printing, acoustophoretic printing and 3D printing. Sensor devices (e.g. pressure sensors, strain sensors, temperature sensors, and electrochemical sensors) employed for wearable healthcare monitoring are summarized. Finally, the key challenges and opportunities of the printed sensors based on liquid metals in personalized healthcare monitoring and human-machine interfaces are also discussed.